Uniform asymptotics for discounted aggregate claims in dependent multi-risk model. Issue 4 (16th February 2019) - Lu, Dawei; Song, Lixin; Li, Fuqi
ABSTRACT: In this paper, we consider a nonstandard renewal multi-risk model where a company has n types of independent insurance contracts and each contract has some dependent claims and stochastic return. The price process of the investment portfolio is described as a geometric Lévy process. When the claim size distribution belongs to the class of C, we can get some asymptotic formulae for the tail probability of n types contracts' discounted aggregate claims and ruin probabilities, holding uniformly for some finite horizons.